THE ROLE OF EMPLOYEES AND HUMAN RESOURCE MANAGEMENT IN CREATING BRAND VALUES - Virijević Jovanović, Saša; Jošanov Vrgović, Ivana B. (International Journal of Economic Practice and Policy, 2017)
Regarding the definitions of brand, which indicate that the purpose of branding is to create long-term relationships with consumers, brand management can be defined as the process of building consumer loyalty towards the brand. A brand is more than just a product. Practice shows that branded products have been built on for many years, by raising the level of quality, and creating a special relationship with consumers. In the process of creating loyal customer there is a great importance of human resources whose skills, competence and empathy influence the brand positioning. Considering the importance of human resource management, the paper explores the role of employees in the process of creating brand value.
Keywords: brand; brand management; brand values; brand awareness; Human resources; human resource management